FIRM SIZE DAN LEVERAGE PADA AUDIT REPORT LAG - Rio Dwi Ananda; Diana Gustinya (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2024)
This study aims to examine the effect of firm size and leverage on audit report lag. The number of research samples is 11 companies obtained by purposive sampling method. The data source of this study is secondary data, in the form of financial reports. The analysis technique used in this study is multiple regression analysis. The results of the analysis show that Firm Size (X1) and Leverage (X2) have an effect on audit report lag. This study is expected to provide benefits for companies and auditors to be able to consider and organize field work so that review preparation can be carried out quickly and accurately so that audit report lag can be minimized as much as possible